IMPLEMENTASI PEMBELAJARAN COOPERATIVE LEARNING DALAM MEMBANGUN EFEKTIVITAS PEMBELAJARAN DI MADRASAH TSANAWIYAH MATLA’UL HUDA ARGOSUKO PONCOKUSUMO - Nadhirotul Ulfa; Azhar Haq; Yorita Febry Lismanda (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Islamic religious education is a characteristic of the curriculum in madrasas. Therefore teachers are required to build an effective classroom atmosphere, so that students feel happy and comfortable, so students can absorb the material well. In this case the selection of learning models is one of the factors that influence the effectiveness of learning in the classroom. This is the background of the Fiqh teacher Mts Matla'ul Huda using cooperative learning models, because the teacher feels helped to condition the class. Researchers used qualitative research with a case study type approach. The data validity checking technique uses a credibility test, namely extended attendance, triangulation, and peer discussions. In this study, the teacher has implemented a cooperative learning model. Several methods of cooperative learning models that have been applied by teachers are Outside-Inside Circle and The Power of Two. Evaluations for learning are carried out routinely at the end of each learner. The teacher evaluates the discipline, prayer procedures and ablution in the students' practical activities which are carried out every morning, these activities take the form of Dhuha prayer and Dhuha prayer in congregation